THE ECONOMIC INFLUENCE OF TSARIST RUSSIA ON THE KHIVA KHANATE: PRESSURE THROUGH TRADE AND POLITICAL INTERFERENCE (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the intervention of Tsarist Russia in the internal political and economic affairs of the Khiva Khanate at the end of the 19th century, based on historical sources. Using documents and other archival materials preserved in the collection of the Ichan-Kala Museum-Reserve, the article reveals the Russian Empire's involvement in Khiva's trade system, particularly its direct influence on tax collection policies.The article discusses the creation of trade privileges for Russian citizens, the establishment of special tax provisions for them, and the strengthening of economic control through the importation of measuring instruments (scales and weights) from Russia. Through historical documents, the article also highlights the active involvement of Russian officials in the internal policies of the Khiva Khanate in areas such as control over alcohol sales, security matters, attacks on caravans, and judicial proceedings.